A Framework for the Evaluation of the Feasibility of Public – Private Partnership in Local Government in Serbia - Sladjana Benkovic; Nemanja Milanovic; Milos Milosavljevic (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The adopton of the New Law for Local Government Financing is currently underway in a Serbian Parliament procedure. The goal of the new law is the creaton of clear government regulatons which will defne the system of fnancing for local government enttes. This will furthermore create an environment of stability and predictability with regard to revenue planning when preparing local government enttes’ budgets, as well as achieving a vertcal balance when distributng revenues amongst various state levels. Additonally, these goals are refected in the establishment of a system to increase the share of public investment in the total expenses of countes and cites, as well as in the vertcal balance with regard to the distributon of revenue and jurisdicton at various state levels. In that sense, it is preferable to understand fnancial models such as public-private partnerships, which have stll not, to an adequate degree, been adopted in Serbia, but one which could potentally contribute to the introducton of additonal sources of local government fnancing. In order to beter perceive the current capacites of this model of fnancing local government in Serbia, a study was conducted during the spring and summer of 2016, taking into account a sample of 150 examinees. The results of the study indicate very low human resource and technical capacites in local government with regard to realizing and comprehending the concept of public-private partnership.